Schizophrenic Speech Potrayed in the Main Character in Canvas Movie - Fais Wahidatul Arifatin (STKIP PGRI Tulungagung, 2023)
This research is focused on the analysis of psycholinguistics aspect. The purpose of the study is to analyze the linguistic phenomena of schizophrenia suffered by the amin character in Canvas movie which is Mary. The objectives of this research is to find out and describe the language abnormalities experienced by the main character. There are some findings related to schizophrenic language abnormalities, from eight types that occur in this research is only five. They are looseness, perseveration of ideas, non-logical reasoning (peculiar logic), weakening of goal, and poverty of speech. Speech abnormalities often appear in the symptoms of someone who has schizophrenia by repeating the same word or phrase over and over again.